Passively Q-switched flashlamp pumped Nd:YAG laser using liquid graphene oxide as saturable absorber - Adnan, N.N.; Bidin, N.; M.Taib, N.A.; Haris, H.; Fakaruddin, M.; Hashim, A.M.; Krishnan, G.; Harun, S.W. (Elsevier, 2016)
The performance of passively Q-switched Nd:YAG laser operating at 1060 nm is demonstrated using liquid graphene oxide (GO) composite solution as saturable absorber for the first time. The Q-switched Nd:YAG laser is pumped by a xenon flashlamp. The GO was prepared using the simplified Hummer's method and then mixed with polyethylene oxide to form a composite solution. The Q-switched pulsed laser operates at wavelength of 1064.5 nm with a threshold pump energy of 33.64 J. The maximum output Q-switched laser energy of 41.6 mJ achieved at the maximum pump energy of 81 J. The corresponding pulse width is 98.67 ns.